1994
DOI: 10.1111/j.1365-2923.1994.tb02714.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadaver dissection on the attitudes of medical students

Abstract: A study was conducted to determine whether the attitudes of medical students to death and caring changed during the 3 months following exposure to cadaver dissection. All first-year students were invited to complete a questionnaire immediately before their initial cadaver dissection experience, after 6 weeks, and after a further 3 months. The questionnaire reflected attitudes to death, violent death, death of someone known to the respondent and caring when someone known to the respondent is seriously injured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
2
18

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 13 publications
5
71
2
18
Order By: Relevance
“…This reflects previous findings that medical students often utilise defensive strategies to minimise anxieties arising from conducting human dissection (e.g., Abu-Hijelh et al, 1997;Charlton et al, 1994;Sanner, 1997). Smith and Kleinman (1989) noted how defensive strategies, such at overly intellectualising the process of human dissection, could allow students to become more involved in the process of learning in which they "gradually come to see the human body as an interesting object, separate from the person" (p. 65).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This reflects previous findings that medical students often utilise defensive strategies to minimise anxieties arising from conducting human dissection (e.g., Abu-Hijelh et al, 1997;Charlton et al, 1994;Sanner, 1997). Smith and Kleinman (1989) noted how defensive strategies, such at overly intellectualising the process of human dissection, could allow students to become more involved in the process of learning in which they "gradually come to see the human body as an interesting object, separate from the person" (p. 65).…”
Section: Discussionsupporting
confidence: 76%
“…However, there was disagreement on whether the experience was essentially traumatic or simply significant for identity formation. More recently, the human dissection experience is seen as a way to educate students about death and dying within a humanistic framework (Marks, Bertman & Penney, 1997;Rizzolo, 2002), particularly as studies confirmed the rapid development of coping mechanisms that could predispose students to distance themselves from patients (e.g., Charlton, Dovey, Jones & Blunt, 1994).…”
mentioning
confidence: 99%
“…It is interesting to note that the majority of the students who had difficulties were female students. This is also reflected in the Indian study 1 as well as in few other studies published previously 2,3,4 .…”
Section: Discussionsupporting
confidence: 59%
“…19 These reactions are aggravated because students are not prepared psychologically for what they see during an autopsy. 7,22 The experience of medical procedures, such as the dissection of a corpse and surgical operations, are frightening and emotionally traumatic. 7 Some students report severe disturbances, such as nightmares, after post-mortem dissections.…”
Section: Discussionmentioning
confidence: 99%